Sport research and the policy movement. Issue 2 (3rd April 2021) - Pielke, Roger; Harris, Spencer
Abstract: The modern policy movement in academia is often traced to the early 1950s in the United States, grounded in intellectual traditions that go back decades and centuries earlier. Since then, numerous schools and sects have developed around the world focussed on teaching, research and practice where academic research encounters public and private decision making. Policy studies, policy analysis, policy evaluation, policy sciences, applied ethics and public affairs are but a few of these sub-disciplines which can rightly claim to focus on developing theory and research methods applicable to the study of policy making and its political and social context. Within this complex tapestry of academic inquiry, a debate has thrived for decades between those who look to inquiry primarily to advance theory and those who utilise inquiry primarily to advance practice. This debate plays out within specific topical areas, such as environmental policy, social policy and international relations. We should expect the study of sport to be no different. This paper looks to the history of the broader policy movement to provide guidance to aspiring researchers of sport policy and governance who seek to bring academic expertise to practical challenges of governance and policy.